Efecto del ph y la concentración de sulfato de cobre sobre la degradación del cianuro de sodio en solución acuosa utilizando el proceso so2 / aire. - Zavaleta García, Luis Gustavo (2014)
This work was carried out at the premises of Mineral Processing Laboratory School of Metallurgical Engineering, Faculty of Engineering; to which a solution of sodium cyanide at a concentration of 942.31 ppm was used. To conduct this work, INCO method was used; which requires as oxidizing sulfur dioxide (SO2), for that sodium bisulfite (NaHSO3) was used. This in water dissociates into sodium hydroxide and sulfur dioxide. As copper ion catalyst II (from the copper sulfate pentahydrate) was used, whose concentrations were 10, 20, 30 and 40 ppm. This required a basic medium, so that the tests were conducted at pH of 9.5, 10, 11 and 12; used a solution of caustic soda (NaOH) at 50%. Each test was performed in a stainless steel vessel with a volume of 2.5 L of cyanide solution; air from a compressor was used to maintain a concentration of 12 ppm oxygen in the solution; work was done at 1000 rpm in the bank agitators; always controlling the pH. Samples were taken every half hour to evaluate the kinetics of the reaction and also add additional reagents, for further degradation of cyanide. Finally, the pH and optimal concentration of copper II tests were 10 and 40 ppm, respectively. Furthermore, the results were a cyanide destruction of 95.3070%.